دور نظرية القيود في حل قيود إدارة المستودعات في الشركات التجارية دراسة تطبيقية - فرحات منى; المجاهد عبد العزيز (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The concept of Theory of Constraints comes as a modern management model that focuses on improving costs by identifying the constraints which limits the business process, in order to eliminate these constrains and weaken their power and by result improving the performance of the company as a whole. This research presents the concepts and literature of this theory from commercial companies’ point of view. The conclusion of this applied research was able to solve many of the constraints that hinder the functioning of warehouse management and thus improve performance. The research depends on descriptive analytical approach. We will review the importance of the Theory of Constraints and its steps and the benefits of its application, and we will present a real-life situation on a warehouse department within a commercial company operating in the Syrian market proving that applying this theory in the business processes will improve solving the constrains and thus reduce costs and increase efficiency. يأتي مفهوم نظرية القيود كنموذج إداري حديث يهتم بتحسين التكاليف عن طريق التعرف على القيود التي تعيق سير الأعمال في الشركة بغية إزالة هذه القيود وإضعاف قوتها، للارتقاء بأداء الشركة ككل. البحث يعمل على طرح مفاهيم وأدبيات نظرية القيود من وجهة نظر الشركات التجارية. وكانت نتيجة البحث ايجابيية حيث استطاعت حل الكثير من القيود التي تعيق سير أعمال إدارة المستودعات وبالتالي تحسين أداءها. يعتمد البحث على المنهج التحليلي الوصفي، حيث سنقوم باستعراض أهمية نظرية القيود وخطواتها وفوائد تطبيقها ثم عرض تطبيق عملي على قسم المستودعات داخل شركة تجارية تعمل في السوق السورية، ومدى انعكاس تطبيق نظرية القيود على حل العقد التي تحول دون عمل هذا القسم بالشكل الأمثل، وتخفيض التكاليف المتعلقة به ورفع كفاءته.